2013
DOI: 10.1123/jpah.10.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Are Older Adults Who Volunteer to Participate in an Exercise Study Fitter and Healthier Than Nonvolunteers? The Participation Bias of the Study Population

Abstract: Background:Participation bias in exercise studies is poorly understood among older adults. This study was aimed at looking into whether older persons who volunteer to participate in an exercise study differ from nonvolunteers.Methods:A self-reported questionnaire on physical activity and general health was mailed out to 1000 persons, aged 60 or over, who were covered by the medical insurance of the French National Education System. Among them, 535 answered it and sent it back. Two hundred and thirty-three pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 38 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…This imminent, global “geriatric boom burden” is particularly pronounced among subpopulations of the VOCODFLEX, reaching the highest rate of disproportionate burden in end‐stage cancer patients (ESC patients) . Furthermore, although the numbers of specialists’ field‐specific clinical guidelines increase, older people are commonly excluded from most randomised controlled trials on which these guidelines are based. Application of all guidelines without regard to the trial populations from which they were created can lead to inappropriate prescribing and polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…This imminent, global “geriatric boom burden” is particularly pronounced among subpopulations of the VOCODFLEX, reaching the highest rate of disproportionate burden in end‐stage cancer patients (ESC patients) . Furthermore, although the numbers of specialists’ field‐specific clinical guidelines increase, older people are commonly excluded from most randomised controlled trials on which these guidelines are based. Application of all guidelines without regard to the trial populations from which they were created can lead to inappropriate prescribing and polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who volunteer for research studies are often more highly educated, have higher socio-economic status and are more sociable. Volunteer bias has been reported in an exercise intervention trial where participants were found to be fitter and healthier than non-volunteers [ 11 ]. Other studies have also suggested that volunteer bias might affect clinical trial results [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that could be contributing to these findings, although speculative, may reflect an issue with selfselection, such that patients who were physically active may have been more likely to participate in this study because it was advertised as being focused on lifestyle behaviors. There is evidence of participation bias in physical activity intervention studies, such that healthier, fitter participants are more likely to participate [56]. Although this study is cross-sectional and based on self-report, the way it was advertised may have contributed to participation bias, which may explain the high number of participants engaging in sufficient levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%